Open Science FAIR Symposium - El-Gebali, Sara (My University, 2021)
Talk from Open Science FAIR Symposium covering the following topics:Overview of Research Data Management (RDM) What is Data? FAIR Principles Where do we start? RDM best practices FAIR vs Open Open Data challenges
Keywords: Research data management; FAIR principles; Open Science